2013
DOI: 10.1038/nn.3353
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII regulates diacylglycerol lipase-α and striatal endocannabinoid signaling

Abstract: The endocannabinoid 2-arachidonoylglycerol (2-AG) mediates activity-dependent depression of excitatory neurotransmission at central synapses; however, the molecular regulation of 2-AG synthesis is not well understood. Here we identify a novel functional interaction between the 2-AG synthetic enzyme diacylglycerol lipase-α (DGLα) and calcium/calmodulin dependent protein kinase II (CaMKII). Activated CaMKII interacts with the C-terminal domain of DGLα, phosphorylates two serine residues, and inhibits DGLα activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 57 publications
3
76
1
Order By: Relevance
“…1b,c p>0.05 by one-sample t-test). This concentration of DHPG is able to augment 2-AG mobilization when combined with brief postsynaptic depolarization (Shonesy et al, 2013). These data suggest that SAG is not converted to an active synaptic pool of 2-AG under these basal conditions and that the main role of mGluR activation is to stimulate production of DAG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b,c p>0.05 by one-sample t-test). This concentration of DHPG is able to augment 2-AG mobilization when combined with brief postsynaptic depolarization (Shonesy et al, 2013). These data suggest that SAG is not converted to an active synaptic pool of 2-AG under these basal conditions and that the main role of mGluR activation is to stimulate production of DAG.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, multiple behavioral studies have demonstrated the importance of endocannabinoid signaling in a variety of physiological functions (Fernandez-Ruiz and Gonzales, 2005; Marsicano et al, 2002; Orio et al, 2009; Patel et al, 2009; Varvel and Lichtman, 2002). On-demand, postsynaptic synthesis and release of endocannabinoids can induce short (Kreitzer and Regehr, 2001; Shonesy et al, 2013) or long-term depression of transmitter release (Gerdeman et al, 2002; Lerner et al, 2010; Lerner and Kreitzer, 2012) through activation of presynaptic type 1 cannabinoid receptors (CB1Rs) (El Manira and Kyriakatos, 2010; Heifets and Castillo, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of single MSNs by depolarizing pulses or action potential trains ( fig. S1), which trigger endocannabinoid (eCB) release (9)(10)(11)(12), induced a transient depression (76.5 ± 2.9% relative to the control EPSC amplitude, P < 0.001) in 16 out of 33 homoneuronal synapses (48.5%) (Fig. 1, B and C).…”
mentioning
confidence: 98%
“…Similar Purkinje neuron depolarization also suppresses the GABAergic synapses from cerebellar cortical interneurons (Tanimura et al, 2010), such as the GABAergic basket cells (Szabo et al, 2004). In addition to the HC and cerebellum, DSI and/or DSE is also observed, e.g., in the VTA DA neurons (Melis et al, 2004), NAc MSNs (Tanimura et al, 2010;Shonesy et al, 2013), and in the BLA neurons (Zhu and Lovinger, 2005;Yoshida et al, 2011;Shonesy et al, 2014). Together these findings suggest that the retrograde eCB signaling is a very general "local" transient process that tunes neurotransmission (reviewed in Wilson and Nicoll, 2002;Kano et al, 2009).…”
Section: H Cannabinoids: Multiple Mechanisms and Possible Indicationsmentioning
confidence: 93%